Analysis of Factors Affecting Demand for LCGC Car in Indonesia - Fitra Ari Pratama Nasution (ProBisnis : Jurnal Manajemen, 2021)
In this thesis, the author takes the title of the research, namely "Analysis of Factors Affecting the Demand for LCGC Cars in Indonesia". The topic is taken based on the phenomenon that occurs in Indonesia that lately people are being served with cheap and environmentally friendly cars, in this case the car manufacturers are paying attention to the earth which is currently polluted with vehicles that produce excess fuel emissions that can cause pollution. destroy ecosystems on earth. By using the OLS (Ordinary Least Square) method in the E-Views 8.0 application program. This study explains the variables of LCGC car prices, competitor car prices, per capita income, interest rates, and advances that affect the demand for LCGC cars in Indonesia. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS), and Gaikindo. The results of this study state that the LCGC car price variable, loan interest rate variable, and down payment variable have a negative and significant effect on the demand for LCGC cars in Indonesia. . Meanwhile, the competitor's car price variable, and the income variable per capita have a positive and significant impact on the demand for LCGC cars in Indonesia.